2023
DOI: 10.1097/hep.0000000000000461
|View full text |Cite
|
Sign up to set email alerts
|

Progression of liver disease and portal hypertension in dyskeratosis congenita and related telomere biology disorders

Abstract: Background and Aims: Dyskeratosis congenita (DC) and related telomere biology disorders (TBD) are characterized by very short telomeres and multisystem organ involvement including liver disease. Our study aimed to characterize baseline hepatic abnormalities in patients with DC/TBD and determine risk factors associated with liver disease progression. Approach and Results: A retrospective review was performed on a cohort of 58 patients (39 males) with DC/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Our cohort demonstrates a similar broad spectrum of liver involvement in earlier studies. 5 , 6 , 17 19 Elevated liver enzymes are a common manifestation seen in the majority of patients. There was a relatively high prevalence of cirrhosis in our cohort (34%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our cohort demonstrates a similar broad spectrum of liver involvement in earlier studies. 5 , 6 , 17 19 Elevated liver enzymes are a common manifestation seen in the majority of patients. There was a relatively high prevalence of cirrhosis in our cohort (34%).…”
Section: Discussionmentioning
confidence: 99%
“…Liver disease in telomere biology disorders is common but poorly characterized. 5 , 6 , 17 A National Institutes of Health study found hepatic involvement in 40% of adult patients with TBD. 18 In the study, which included adults aged 29–50 years, the most common laboratory findings were liver enzyme elevations and cholestasis, and the most common imaging findings were increased hepatic echogenicity and hepatomegaly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation